2014
DOI: 10.1371/journal.pone.0092456
|View full text |Cite|
|
Sign up to set email alerts
|

A Genome-Wide Perspective of miRNAome in Response to High Temperature, Salinity and Drought Stresses in Brassica juncea (Czern) L

Abstract: Micro RNAs (miRNAs) are involved in diverse biological processes including adaptive response towards abiotic stresses. To unravel small RNAs and more specifically miRNAs that can potentially regulate determinants of abiotic stress tolerance, next generation sequencing of B. juncea seedlings subjected to high temperature, high salt and drought conditions was carried out. With the help of UEA sRNA workbench software package, 51 conserved miRNAs belonging to 30 miRNA families were identified. As there was limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 90 publications
(72 reference statements)
4
33
0
Order By: Relevance
“…It would be interesting to know if different miRNAs have interactions in plant responses to abiotic stress. To this end, stem-loop RT-qPCR was conducted to analyze several conserved miRNAs that are implicated in plant abiotic stress responses, including miR396, miR156, and miR172 (Wu et al, 2009a;Gao et al, 2010;Hackenberg et al, 2012;Liang et al, 2012;Bhardwaj et al, 2014;Cui et al, 2014;Gupta et al, 2014;Pandey et al, 2014;Xie et al, 2015). Figure 11, A to C, shows that miR396, miR156, and miR172 were all down-regulated in transgenic plants overexpressing Osa-miR528, suggesting a potential cross talk of miR528 with other miRNAs in the regulatory network to orchestrate the plant response to stress.…”
Section: Mir528 Has Cross Talk With Other Abiotic Stress-related Mirnmentioning
confidence: 99%
“…It would be interesting to know if different miRNAs have interactions in plant responses to abiotic stress. To this end, stem-loop RT-qPCR was conducted to analyze several conserved miRNAs that are implicated in plant abiotic stress responses, including miR396, miR156, and miR172 (Wu et al, 2009a;Gao et al, 2010;Hackenberg et al, 2012;Liang et al, 2012;Bhardwaj et al, 2014;Cui et al, 2014;Gupta et al, 2014;Pandey et al, 2014;Xie et al, 2015). Figure 11, A to C, shows that miR396, miR156, and miR172 were all down-regulated in transgenic plants overexpressing Osa-miR528, suggesting a potential cross talk of miR528 with other miRNAs in the regulatory network to orchestrate the plant response to stress.…”
Section: Mir528 Has Cross Talk With Other Abiotic Stress-related Mirnmentioning
confidence: 99%
“…Among these studies, the miR164 family was reported to target six NAC family members, of which four had negative effects on drought tolerance in rice seedlings (Fang et al 2014b). In Brassica , miR164 was shown to target a NAC TF, whose expression was negatively correlated with miR164 under drought, salinity, and high-temperature stresses (Bhardwaj et al 2014). Additionally, maize miR164 contributed to lateral root development through cleavage of a target NAC TF (J. Li et al 2012), which also suggests a role in abiotic stress responses, given the role of roots in drought and salinity responses.…”
Section: Mirna and Stress Regulation Mechanismsmentioning
confidence: 99%
“…shown to be conserved across Poaceae, yet only three (miR162, miR164, miR397), which are known to be highly conserved through Viridiplantae, were previously shown to be drought responsive in other plants (Liu et al 2009;Zhou et al 2010;Capitão et al 2011;Burklew et al 2012;Ferreira et al 2012;Sun et al 2012;Wang et al 2013;Bhardwaj et al 2014;Ghorecha et al 2014;Fang et al 2014). Drought-related changes in the expressions of two (miR164, miR397) were even reported in bread wheat (Gupta et al 2014).…”
mentioning
confidence: 99%